The teaching of modern languages in France and francophone Switzerland (1740–1940): a historiographical overview*. Issue 1 (1st January 2018) - Extermann, Blaise
ABSTRACT: This paper has two aims: firstly, it sketches the history of language teaching in France and francophone Switzerland over a period of 200 years, with a particular focus on the teaching of German. Secondly, it seeks to shed light on some of the francophone historiographical approaches which have influenced recent research in this area. Historical sociolinguistic studies have highlighted the multilingual nature of the Ancien Régime. Mainstream conclusions from the history of language teaching methodology have been complemented by contributions from sociolinguistics which shed light on the developing status of teachers, their working conditions, their role in educational institutions and their professionalisation during the nineteenth century. From the beginning of the twentieth century, despite the dominance of monolingual ideology, discussion of modern language teaching started to take place transnationally. Today, historians are also working across borders in order to get a more accurate picture of the development of language teaching.